Aux seuils du monde animal : le bestiaire médiéval du péritexte au métatexte - Yoan Boudes (Perspectives Médiévales)
The peritextual apparatus described by Gérard Genette is an integral part of medieval book production and medieval studies are equiped to treat these productions in the manuscripts they study, whatever the genres are transmitted by them. However, the genettian terminology is not exactly new to medieval studies and the description of “page layout”, or mise en page is often prefered so as to describe the particularity of pre-print culture. This paper would like to measure the relevance of Genette’s theory through the example of French bestiaries production in order to understand the benefit of the use of peritext as a concept. These didactic texts can, indeed, be fruitfully extended in the peritextual productions of the manuscripts: mainly, they allow a visual and figurative actualization of the ethical and poetic voice of the clerical personality of the author. If, in the genettian approach, the peritext is a contractual space between the author and the recipients of the text, medieval textuality redefines the relationship at stake: it is much more the scribes who are proposing a way of reading for the patrons and the audience. The peritext is then a link between different types of readers, performing the meaning and the efficiency of bestiary texts. Less than a place, the peritext seems to be a relationship on the manuscript’s pages: the relevance of Genette’s paratextual theory – quite redundant for textual description or realization of the material context of the text – is much more fruitfull when it comes to understand it as a dialogue and a dynamic.